2015
DOI: 10.1155/2015/907379
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Fixed-Bed Column Study and Adsorption Modeling: Removal of Lead Ion from Aqueous Solution by Charcoal Originated from Chemical Carbonization of Rubber Wood Sawdust

Abstract: The efficiency of chemically carbonized rubber wood sawdust for the removal of lead ion from the aqueous stream was investigated by column process. Chemically carbonized rubber wood sawdust was prepared by treating the sawdust with H2SO4and HNO3. Maximum removal of lead ion in column process was found as 38.56 mg/g. The effects of operating parameters such as flow rate, bed depth, concentration, and pH were studied in column mode. Experimental data confirmed that the adsorption capacity increased with the incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 22 publications
6
47
0
2
Order By: Relevance
“…Conversely, with an increase in bed depth, the residence time of Pb(II) solution inside the column was increased, allowing the Pb(II) ions to diffuse deeper into the fungal biomass (Babu et al, 2010). The related affinity was also reported in the literature (Biswas & Mishra, 2015). A plot of service time vs. bed depth, at a flow rate of 1 mL min −1 (Figure 4-60b) was linear.…”
Section: Effect Of Bed Height (Bdst Model)supporting
confidence: 85%
“…Conversely, with an increase in bed depth, the residence time of Pb(II) solution inside the column was increased, allowing the Pb(II) ions to diffuse deeper into the fungal biomass (Babu et al, 2010). The related affinity was also reported in the literature (Biswas & Mishra, 2015). A plot of service time vs. bed depth, at a flow rate of 1 mL min −1 (Figure 4-60b) was linear.…”
Section: Effect Of Bed Height (Bdst Model)supporting
confidence: 85%
“…Another simplified numerical model used to describe fixed-bed column adsorption data is the modified dose response model (MDRM). This model basically diminishes the error resulting from the use of the Thomas model, particularly at lower or higher time periods of the breakthrough curve (Lee et al 2015;Biswas and Mishra 2015).…”
Section: Adsorption Models For Column Studymentioning
confidence: 99%
“…Research has shown that increasing the concentration of elements leads to shorter breakthrough volume and exhaustion time because of a higher driving force of elements that can overcome the mass transfer resistance in the liquid phase. Moreover, saturation can be reached faster with high concentrations and leads to mobility of the elements in the soil which can end up in the groundwater . The particular concentrations were chosen since elements were found to be in high concentrations in the area under study .…”
Section: Methodsmentioning
confidence: 99%
“…Shows the end of simulation Exchange Defines the exchange composition or the cation exchange capacity Transport Specify parameters for the advectivedispersive-reaction transport Use Select aqueous solution that or reactants that are considered at a particular stage during the run Print Selected data blocks that will be printed on the output file because of a higher driving force of elements that can overcome the mass transfer resistance in the liquid phase. Moreover, saturation can be reached faster with high concentrations and leads to mobility of the elements in the soil which can end up in the groundwater [25,26]. The particular concentrations were chosen since elements were found to be in high concentrations in the area under study [14].…”
Section: Abstract Functionsmentioning
confidence: 99%